Non-anthropocentric poetics in John Banville's art trilogy - Choo, Gladis Hui Li (2014)
Since Descartes' cogito ergo sum takes the self-reflexive "I" as the guarantor of its existence and the basis of all things, it may be considered an anthropocentric philosophy. As a critique of the anthropocentrism that underpins Descartes' philosophy, Heidegger's conception of the aesthetic interpellates itself within an anti-humanist tradition that locates the human within a universe which pre-exists it, thereby revealing the limitations of the Cartesian mode of seeking after empirical knowledge. These limitations surface most obviously in the observation of the world's resistance to our attempts to subjugate it under totalising concepts, rendering itself infinitely strange and ungraspable to the inquiring Cartesian subject. The sheer indifference of nature to the human world should further debunk the view that takes the human as the world's ontological centre. Given the decentred condition of the human, which renders the notion of human volition tenuous, Heidegger's non-anthropocentric conception of the aesthetic offers a possibility of transcending this tedium. This possibility is evinced in Heideggerean poiesis, which refers to a bringing forth, by which the artist may realise his volition, however fleetingly, as an interdependent achievement vis-à-vis the autonomous art object that he leads to being. The realisation of this volition is contingent upon the artist's understanding of his ontological standpoint as what Heidegger calls "Being-in-the-world", a standpoint which recognises his situatedness in the world, that his being is always defined vis-à-vis the world itself. Given that much of John Banville's oeurve feature the decentred subject as suspended in an indifferent world, this paper seeks to trace the assimilation of this non-anthropocentric aesthetic specifically in the art trilogy, even as the novels foreground differing sets of meditations on the imagination and the significance of art.